PENGARUH PEMUPUKAN N, P DANK TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum. L) VARIETAS BIMA BREBES DANTHAILAND DI TANAH ULTISOL - Irawan, Dodi; Idwar, Idwar; Murniati, Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aims to determine the effect of N, P and K on the growth and yield of Bima Brebes and Thailand varieties onion and the best dosage to support in ultisol soil. This research has been conducted in the field of Agricultural Extension Center, Geringging Village. Kampar Kiri, Kampar District, Riau Province. This study was conducted in 2x4 factorial experiment arranged in a randomized completely block design (RCBD) comprises two factors. The first factor is varieties consisting of two levels is Bima Brebes and Thailand. The second factor is the dose of fertilizer, N, P, and K comprising 4 levels, namely: urea 250+ TSP 150 + KCl 100 kg/ ha, urea 500 + TSP 300 + KCl 200 kg/ha, urea 750  + TSP 450 + KCl 300 kg/ha dan urea 100 + TSP 600 + KCl 400 kg/ha. Parameters measured were dry weight, weight of tuber per hill, tuber number, tuber wrap, fresh tuber weight per plot and the weight of feaseable storage of tuber per plot. The result showed that the Thailand varieties of urea fertilizer and 1000 kg/ha + TSP 600 kg/ha + KCl 400 kg/ha gives the highest yield of onion crop.Keywords : Onion, Ultisol Soil, Fertilizer N, P and K.